1983
DOI: 10.1111/j.1432-1033.1983.tb07237.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase: Interaction of RNA and Rifampicin with the Subassembly α2β

Abstract: We studied the inhibition of tryptic digestion of the subassembly x2/1 of Esclwichiu coli DNA-dependent RNA polymerase to investigate its interaction with RNA and rifampicin. Both agents decreased distinctly the cleavage of subunit lj in the subassembly as well as the degradation of the transiently formed polypeptides ( M , > 80000). Short RNAs with a chain length of approximately 35 nucleotides were most protective at a concentration of 1 m d m l while long. RNAs were less effective at the same concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Early biochemical experiments demonstrated that, in agreement with our data, rifampicin derivatives cross-link to ␤ nonspecifically (20). On the other hand, it has been reported that ␣ 2 ␤ weakly binds Rif as judged by spectral, gel filtration-based, and proteolytic assays (21,22). However, in these later studies the authors did not determine whether their ␣ 2 ␤ preparation was free of traces of the RNAP core and whether the observed interaction was specific because no controls using ␣ 2 ␤ containing the ␤ subunit carrying a Rif resistance mutation were used.…”
Section: Figsupporting
confidence: 91%
“…Early biochemical experiments demonstrated that, in agreement with our data, rifampicin derivatives cross-link to ␤ nonspecifically (20). On the other hand, it has been reported that ␣ 2 ␤ weakly binds Rif as judged by spectral, gel filtration-based, and proteolytic assays (21,22). However, in these later studies the authors did not determine whether their ␣ 2 ␤ preparation was free of traces of the RNAP core and whether the observed interaction was specific because no controls using ␣ 2 ␤ containing the ␤ subunit carrying a Rif resistance mutation were used.…”
Section: Figsupporting
confidence: 91%